Impact of Financial Literacy on Financial Well-being: A Study of Public Sector Employees - Tharsanan, P.; Balagobei, S. (Sri Lanka Finance Association., 2023)
The study aims to investigate the impact of financial literacy on financial well- being of public sector employees in Jaffna district. For data analysis, two hundred public sector employees in Jaffna district were selected as samples using a cluster sampling technique, and primary data was collected through a structured questionnaire. Financial literacy consists of three dimensions such as financial knowledge, financial behaviour and financial attitude whereas financial well-being is measured by individual economic behaviour, financial awareness and financial perception. Data were analyzed using correlation and multiple regression techniques to examine the hypotheses of this study. The results reveal that financial literacy positively impacts the financial well-being of public sector employees in Jaffna district. The findings recommend financial education programs focusing primarily on enhancing financial knowledge, behaviours and attitude to facilitate the financial well-being of public sector employees.
Keywords: Financial attitude; Financial behaviour; Financial knowledge; Financial literacy; Financial well-being